The next wave in ERP implementation - SIAU, Keng (Institutional Knowledge at Singapore Management University, 2001)
Although the benefits of ERP are obvious, the risks and costs associated with it are very high. Some problems in implementing ERP system are documented, but the real challenge comes from the Internet and E-business. ERP is an enterprise wide system whose purpose is to achieve internal efficiency, while E-business cuts across different enterprises and extends the individual value chain into an Internet based, dynamic process aimed at maximizing external efficiency. To survive the E-business challenge, the arguably single, and also the best, solution for ERP systems is to integrate with E-business applications, which we call ERP II. By properly resolving the issues of integration via newly emerged technologies, and embracing the extended function of mobile-commerce, ERP II will continue to flourish in the next century.